Alanine Aminotransferase as a Monitoring Biomarker in Children with Nonalcoholic Fatty Liver Disease: A Secondary Analysis Using TONIC Trial Data - Idil Arsik; Jennifer K. Frediani; Damon Frezza; Wen Chen; Turgay Ayer; Pinar Keskinocak; Ran Jin; Juna V. Konomi; Sarah E. Barlow; Stavra A. Xanthakos; Joel E. Lavine; Miriam B. Vos (MDPI AG, 2018)
Background: Validated noninvasive biomarkers to assess treatment response in pediatric nonalcoholic fatty liver disease (NAFLD) are lacking. We aimed to validate alanine aminotransferase (ALT), a monitoring biomarker for change in liver histology. Methods: A retrospective analysis using data from the TONIC trial. NAFLD histologic assessments were defined by: Fibrosis score, NAFLD activity score (NAS), nonalcoholic steatohepatitis (NASH), and a combination of NASH resolution and fibrosis (NASH + fibrosis). Analysis was performed using classification and regression trees (CART) as well as logistic regression. Results: Mean ALT for the child over 96 weeks and percent change of ALT from baseline to 96 weeks were significant predictors of progression of NAFLD for each histologic assessment (p < 0.001 for fibrosis score, NASH, and NASH + fibrosis and p < 0.05 for NAS). Mean ALT adjusted for age, sex and ethnicity was a better predictor for change in NASH (81.8 (11.0) ROC (receiver operating characteristic curve) mean (SD (Standard derivation))) and NASH + fibrosis (77.8 (11.2)), compared to change in NAS (63 (17.7)) and fibrosis (58.6 (11.1)). Conclusion: Mean ALT over 96 weeks is a reasonable proxy of histologic improvement of NASH and NASH + fibrosis. These findings support ALT as a valid monitoring biomarker of histologic change over time in children with NASH and fibrosis.